Conveying member, drying device, and printing device
Patent Information
- Application Number
- JP2020180513
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-28
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-10-28
AI Technical Summary
【0007】 本発明によれば、表面層にフッ素樹脂を有する搬送部材を長期使用した場合であっても、搬送部材と被接触部材との接触により生じる、被接触部材における接触表面の部分的破壊が抑制される搬送部材を提供することができる。
Smart Images

Figure 0007631732000004 
Figure 0007631732000005 
Figure 0007631732000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a conveying member, a drying device, and a printing device. [Background technology]
[0002] Inkjet printing devices and the like are provided with a transport means for transporting recording media such as continuous paper and cut paper. This transport means guides the recording media to a means for applying a liquid composition such as ink, a means for heating and drying the applied liquid composition, and the like. For example, a cylindrical roller made of an aluminum alloy is used as the transport means.
[0003] Patent Document 1 discloses a drying device having a plurality of transport rollers in a transport path.
[0004] Patent Document 2 discloses a fixing device using a roller whose surface is made of a coating obtained by anodizing aluminum, and in which a solid lubricant such as a fluororesin is impregnated and formed into a film through fine pores in the coating and on the surface of the coating. Summary of the Invention [Problem to be solved by the invention]
[0005] However, in a transport member that transports a contacted member by coming into contact with the contacted member and that has a fluororesin on its surface layer, the fluororesin on the surface layer peels off over time with long-term use of the transport member, and when the contacted member comes into contact with the transport member in which the ratio of the area of the fluororesin to the area of the surface layer has decreased, there is a problem that the contact surface of the contacted member may be partially destroyed. [Means for solving the problem]
[0006] The present invention relates to a transport member that transports a contacted member by coming into contact with the contacted member, the transport member having a surface layer that contacts the contacted member, the surface layer having a support layer having a plurality of recesses on its surface and a fluororesin adhered to the support layer, the proportion of the area where the fluororesin is present being 23.0% or more of the area of the surface layer, and the support layer containing anodized aluminum sulfate. Effect of the Invention
[0007] According to the present invention, a conveying member having a surface layer made of a fluororesin can be provided in which partial destruction of the contact surface of the contacted member caused by contact between the conveying member and the contacted member is suppressed even when the conveying member is used for a long period of time. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a photograph showing an example of a cross section of a support layer having recesses. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a printing device that uses continuous paper. [Diagram 3] FIG. 3 is a schematic diagram showing the contacted member in contact with the conveying member. [Figure 4] FIG. 4 is an SEM image of the surface of the conveying member of Example 1 before the contact friction test. [Diagram 5] FIG. 5 is an SEM image of the surface of the conveying member of Example 1 after the contact friction test. [Figure 6] FIG. 6 shows the results of EDS elemental analysis of the surface of the transport member of Example 1 before the contact friction test. [Figure 7] FIG. 7 shows the results of EDS elemental analysis of the surface of the conveying member of Example 1 after the contact friction test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, one embodiment of the present invention will be described.
[0010] <<Transportation parts>> The transport member of the present embodiment is a member that transports a contacted member by contacting the contacted member. The transport member is a member having a surface layer that contacts the contacted member. The surface layer is preferably provided on a base material. The transport member may or may not have a heating means for applying heat to the contacted member through the surface layer. When the transport member has a heating means, the transport member is preferably a member that heats and dries the liquid composition applied to the contacted member by contacting the contacted member while transporting the contacted member.
[0011] <Surface layer> The surface layer is a layer that comes into contact with a contacted member, and comprises a support layer having a surface including a plurality of recesses and non-recesses, which are areas other than the recesses, and a fluororesin adhered to and supported by the support layer, and may have other components as necessary.
[0012] -Support layer- The support layer is a layer that supports a fluororesin. The support layer is a layer that contains anodized aluminum sulfate as a constituent material (in other words, an anodized aluminum sulfate film), and may contain other constituent materials as necessary. Here, "containing anodized aluminum sulfate" means that a material derived from anodized aluminum sulfate treatment is contained, and the anodized aluminum sulfate treatment is a treatment of anodizing aluminum in an aqueous sulfuric acid solution. That is, the layer that contains a material derived from anodized aluminum sulfate treatment is a layer that contains aluminum oxide and in which a sulfur component is detected. Here, "detecting a sulfur component" means that, for example, when mapping of the sulfur component is performed on a cross section of the support layer, data indicating the presence of the sulfur component is obtained. A specific example of a method for mapping the sulfur component is a method of performing EDS elemental analysis on a cross section of the support layer. As a method for confirming that the layer contains anodized aluminum sulfate (in other words, a layer containing aluminum oxide and in which sulfur components are detected), for example, mapping of the sulfur component, aluminum component, and oxygen component is performed on the cross section of the support layer, and data showing that the sulfur component, aluminum component, and oxygen component are present in the same region can be obtained. Specifically, a method for mapping the sulfur component, aluminum component, and oxygen component by performing EDS elemental analysis on the cross section of the support layer can be used.
[0013] As described above, the support layer is a layer containing anodized aluminum sulfate, so that a plurality of recesses can be formed on the surface. The recesses are structures derived from the anodized aluminum sulfate treatment, and it is preferable in terms of manufacturing that no separate treatment is provided to form the recesses. Here, the recesses are explained with reference to FIG. 1. FIG. 1 is a photograph showing an example of a cross section of a support layer having recesses. As shown in FIG. 1, the recesses represent a recessed structure formed on the surface of the support layer. Also, as shown in FIG. 1, it is preferable that a fluororesin F is attached to the recesses. The fluororesin may also be attached to non-recessed areas, which are areas other than the recesses.
[0014] Here, the reason why it is preferable that the fluororesin is adhered to the support layer will be explained, and also the reason why it is preferable that the fluororesin is adhered to the recesses in the support layer in particular will be explained. In the present embodiment, a conveying member that conveys a contacted member by contacting the contacted member has a problem that the contact surface of the contacted member is partially destroyed as the contacted member comes into contact with the conveying member. This problem is prominent when the contacted member has an area to which a liquid composition is applied and the area is in direct contact with the conveying member, so such a case will be described as an example. The area of the contacted member to which the liquid composition is applied is usually in a somewhat dried state when it comes into contact with the conveying member, but when the area is insufficiently dried, when the area comes into contact with the conveying member and then separates, the liquid composition in the area is transferred to the conveying member side due to interaction with the conveying member, and the area is partially destroyed. In addition, when the area is an image, this is also referred to as "image defect" in the present disclosure. To address this issue of the contact surface of the contacted member being partially destroyed, an effective method is to construct at least a portion of the surface of the conveying member from a fluororesin, thereby reducing the interaction between the contacted member and the conveying member. However, simply providing the fluororesin partially on the surface of the transport member may result in the fluororesin being separated from the surface of the transport member over time due to contact with the contacted member over a long period of time, causing the above-mentioned problems to become apparent again. Therefore, it is more preferable to attach the fluororesin to the recesses in the support layer to prevent the fluororesin from being separated.
[0015] The ratio of the area where the fluororesin is present is 23.0% or more with respect to the area of the surface layer. When it is 23.0% or more, the fluororesin migrates to be embedded in the recesses over time with the long-term contact between the conveying member and the contacted member, and the fluororesin spreads and adheres in an elongated state even in areas other than the recesses (non-recesses). This suppresses the detachment of the fluororesin over time, and also suppresses the decrease in the ratio of the area of the fluororesin in the surface layer. As a result, the problem of partial destruction of the contact surface of the contacted member can be solved. Note that the ratio of the area where the fluororesin is present is preferably 75.0% or less with respect to the area of the surface layer. By making it 75.0% or less, it is possible to suppress the fluororesin from being crushed and becoming tacky due to long-term use of the conveying member, which causes partial destruction of the contact surface of the contacted member. Here, the ratio of the area where the fluororesin exists represents the ratio of the area where the fluororesin exists to the area of the surface layer in an image of the surface layer viewed in plan. The area where the fluororesin exists can be calculated, for example, as follows. First, mapping of the fluorine components is performed on the surface layer of the transport member. A specific example of a method for mapping the fluorine components is a method of performing EDS elemental analysis. Next, the area where the fluororesin exists is calculated from the obtained data using analysis software. Similarly, the area where the fluororesin exists is calculated at any five points, and the average value of these values is adopted. Next, the average value is divided by the area of the surface layer used to calculate the area where the fluororesin exists to calculate the ratio of the area where the fluororesin exists. The area where the fluorine components exist represents an area where the fluorine atom concentration is 1% or more. The measurement area in the EDS elemental analysis can be, for example, 100 μm×100 μm. The proportion of the area where the fluororesin is present is determined for transport members that have not been substantially used, which includes not only transport members that have never been used, but also transport members that have been used on a trial basis or in a small amount, such as transport members immediately after manufacture or transport members that are commercially available.
[0016] The ratio of the area where the fluororesin is present in the regions other than the recesses (non-recesses) is 3.0% or more relative to the area of the surface layer. If it is 3.0% or more, the fluororesin spreads and adheres in an elongated state over time in the non-recesses due to contact between the conveying member and the contacted member over a long period of time. This also suppresses a decrease in the ratio of the area of the fluororesin in the surface layer. As a result, partial destruction of the contact surface of the contacted member is suppressed. Note that the ratio of the area where the fluororesin is present in the non-recesses is preferably 50.0% or less relative to the area of the surface layer. By making it 50.0% or less, it is possible to suppress partial destruction of the contact surface of the contacted member due to the fluororesin being crushed and becoming tacky due to long-term use of the conveying member. Here, the ratio of the area where the fluororesin adhering to the non-recessed portion exists represents the ratio of the area where the fluororesin adhering to the non-recessed portion exists to the area of the surface layer in an image of the surface layer viewed in plan. The area where the fluororesin adhering to the non-recessed portion exists can be calculated, for example, as follows. First, an SEM image is obtained on the surface layer of the transport member to grasp the recessed portion and the non-recessed portion. The SEM image can be obtained by observing at, for example, 2000 times. Next, mapping of the fluorine component is performed on the surface layer of the transport member (within the range where the SEM image is obtained). A specific example of a method for mapping the fluorine component is a method of performing EDS elemental analysis. Next, the area where the fluororesin adhering to the non-recessed portion exists is calculated from the data obtained using analysis software and the SEM image. In the same manner, the area where the fluororesin adhering to the non-recessed portion exists is calculated at any five points, and the average value of these values is adopted. Next, the average value is divided by the area of the surface layer region used to calculate the area where the fluororesin adhering to the non-recessed portion exists to calculate the ratio of the area where the fluororesin adhering to the non-recessed portion exists. The region where fluorine components are present refers to a region where the fluorine atom concentration is 1% or more. The measurement area in the EDS elemental analysis can be, for example, 100 μm×100 μm. The ratio of the area where the fluororesin adhered to the non-recessed portion exists is determined for a transport member that has not been substantially used. Note that a transport member that has not been substantially used includes not only a transport member that has never been used, but also a transport member that has been used for a trial or a small amount of time, such as a transport member immediately after manufacture or a transport member that is commercially available.
[0017] The transport member may have a built-in heating means such as a halogen lamp heater, and the surface temperature may be high (e.g., 100°C or higher) during use. In addition, the transport member may not have a heating means, but a heating member that is a separate member from the transport member may be provided near the transport member, and the surface temperature may be high (e.g., 100°C or higher) during use. In this way, when a conveying member is used in an environment where the surface temperature of the conveying member becomes high, simply providing a fluororesin on the surface of the conveying member will soften the fluororesin that makes up the surface, and as the contacted member is conveyed, the fluororesin will tend to peel off from the surface of the conveying member over time, making the above-mentioned problem of partial destruction of the contact surface of the contacted member more likely to become apparent. Furthermore, in an environment where the surface temperature of the transport member is high, if the contacted member has an area to which the liquid composition is applied and that area comes into contact with the transport member, the tack force between the transport member and the contacted member becomes large, and when that area comes into contact with the transport member and then separates, the liquid composition in that area is transferred to the transport member side due to interaction with the transport member, making that area more likely to be partially destroyed. On the other hand, when a conveying member is used in which the fluororesin is adhered to the support layer as described above and the ratio of the area where the fluororesin is present to the area of the surface layer is 23.0% or more, even if the surface temperature of the conveying member becomes high during use, separation of the fluororesin from the surface of the conveying member over time as the contacted member is conveyed is suppressed, which is preferable. The temperature of the surface layer of the transport member is preferably 100° C. or higher and 140° C. or lower.
[0018] The depth of the recess is preferably 0.4 μm or more and 1.0 μm or less, and more preferably 0.5 μm or more and 1.0 μm or less. When the depth of the recess is within the above range and the ratio of the area where the fluororesin is present to the area of the surface layer is 23.0% or more, the fluororesin is more likely to migrate and be embedded in the recesses over time as the conveying member and the contacted member contact each other for a long period of time. This further suppresses the separation of the fluororesin over time. The depth of the recess can be determined, for example, as follows. First, a surface piece of 5 mm x 5 mm is cut out from the center of the conveying member in the longitudinal direction, and an image of the surface piece (x100) is obtained using an Olympus three-dimensional measuring laser microscope LEXT. Next, the image is analyzed using the attached analysis software OLS4100, and Ra (arithmetic mean height) is calculated. Similarly, Ra is calculated at any 10 points, and the average of these is determined as the depth of the recess.
[0019] The thickness of the support layer is preferably 25.0 μm or more and 35.0 μm or less. By making the thickness of the support layer 25.0 μm or more and 35.0 μm or less, it is possible to achieve both the rigidity of the conveying member and the formation of a recess shape, and it is possible to suppress the detachment of the fluororesin for a longer period of time, and as a result, it is possible to further suppress partial destruction of the contact surface of the contacted member. The thickness of the support layer can be determined, for example, as follows. First, a test piece of 5 mm x 5 mm is cut out from the center of the longitudinal direction of the transport member, and a cross-sectional image (x100) of the test piece is obtained using an Olympus 3D measuring laser microscope LEXT. Next, the support layer portion is determined from the cross-sectional image, and the length of the perpendicular line drawn from the support layer surface toward the substrate is measured in the support layer using the attached analysis software. Similarly, the lengths at 10 arbitrary points are measured, and the average of these is taken as the thickness of the support layer.
[0020] As described above, the support layer is preferably a layer containing anodized aluminum sulfate, since the hardness can be improved compared to a layer containing aluminum oxide produced by a process other than anodized aluminum sulfate. This can improve the hardness of the transport member having the support layer. Specifically, the Vickers hardness of the transport member is preferably 350Hv or more and 450Hv or less. By having the Vickers hardness of the transport member be 350Hv or more and 450Hv or less, wear of the uneven shape of the transport member surface is suppressed, and the uneven shape provides a spacer effect that suppresses the detachment of the fluororesin adhering to the recesses when the transport member and the contacted member come into contact with each other, thereby suppressing the detachment of the fluororesin for a longer period of time, and as a result, the contact surface of the contacted member can be more effectively prevented from being partially destroyed. The Vickers hardness can be measured according to the test method of JIS Z2244.
[0021] -Fluoroplastics- The fluororesin can improve the lubricity between the transport member and the contacted member. As described above, the fluororesin adheres to the support layer, and the ratio of the area where the fluororesin is present to the area of the surface layer is 23.0% or more, so that the fluororesin is prevented from coming off over time and the ratio of the area of the fluororesin in the surface layer is also prevented from decreasing.
[0022] Examples of fluororesins include tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers (PFA, melting point 300 to 310°C), polytetrafluoroethylene (PTFE, melting point 330°C), tetrafluoroethylene-hexafluoropropylene copolymers (FEP, melting point 250 to 280°C), ethylene-tetrafluoroethylene copolymers (ETFE, melting point 260 to 270°C), polyvinylidene fluoride (PVDF, melting point 160 to 180°C), polychlorotrifluoroethylene (PCTFE, melting point 210°C), tetrafluoroethylene-hexafluoropropylene-perfluoroalkyl vinyl ether copolymers (EPE, melting point 290 to 300°C), and mixtures containing these polymers, with polytetrafluoroethylene (PTFE) being preferred.
[0023] The method for adhering the fluororesin to the support layer is not particularly limited, but examples thereof include the following methods. First, a member on which a support layer has been formed is immersed in a dispersion liquid containing fluororesin particles to adhere the fluororesin to the support layer, and then the surface of the member is polished with a soft nonwoven fabric with low water absorption. The nonwoven fabric is preferably one that does not leave fiber residue on the surface of the member, and examples thereof include a polyester-nylon mixed fiber sheet.
[0024] <Base material> The substrate is located on the side of the surface layer that does not come into contact with the contacted member. In addition, during the manufacture of the conveying member, it is preferable that the substrate is treated with sulfuric acid to form the support layer. Therefore, it is preferable that the material constituting the substrate contains aluminum. In addition, it is more preferable that the material constituting the substrate contains magnesium in addition to aluminum. When aluminum is treated with sulfuric acid, aluminum oxide grows in a columnar shape, but by containing magnesium, the growth direction of the aluminum oxide can be disturbed, stress is generated in the aluminum oxide, and the surface of the support layer formed can be made more uneven. Furthermore, it is more preferable that the material constituting the substrate contains silicon in addition to aluminum. By containing silicon, like magnesium, the growth direction of the aluminum oxide can be disturbed, stress is generated in the aluminum oxide, and the surface of the support layer formed can be made more uneven. As described above, by making the surface of the support layer to have a more uneven shape, the uneven shape provides a spacer effect that prevents the fluororesin adhering to the recesses from detaching when the conveying member and the contacted member come into contact, making it possible to prevent the fluororesin from detaching for a longer period of time, and as a result, it is possible to further prevent partial destruction of the contact surface of the contacted member.
[0025] The shape of the substrate is not particularly limited, but is preferably, for example, a long metal rod, and more preferably, a roller shape such as a cylinder or cylindrical body with a circular cross section. By using such a shape of the substrate, the conveying member can be used as a conveying roller. When a roller-shaped substrate is used, the diameter of the circle of the cross section of the conveying member is preferably 50 mm or more and 600 mm or less. By having a diameter of 50 mm or more, the pressure per unit area generated between the conveying member and the contacted member is reduced, and the detachment of the fluororesin is suppressed. On the other hand, by having a diameter of 600 mm or less, excessive adhesion generated between the conveying member and the contacted member is reduced, and thus partial destruction of the contact surface of the contacted member can be further suppressed.
[0026] <Heating means> As described above, the conveying member may have a heating means, but may not have one. Here, the heating means is a means for applying heat to the contacted member through the surface layer, and for example, when the shortest length from a predetermined position of the heating means to the surface layer is compared with the shortest length from the predetermined position of the heating means to the contacted member, the shortest length from the predetermined position of the heating means to the surface layer is shorter. Therefore, for example, when the conveying member is in the form of a roller, the heating means is provided inside the roller-shaped base material and applies heat to the contacted member through the base material and the surface layer. In this way, since the heating means is configured to apply heat to the contacted member through the surface layer, the surface layer becomes in a high temperature state, and generally, the fluororesin provided on the surface of the conveying member becomes easy to separate. However, as in the present disclosure, since the fluororesin adheres to the support layer and the ratio of the area where the fluororesin is present is 23.0% or more relative to the area of the surface layer, even if the temperature of the surface of the conveying member becomes high during use, the separation of the fluororesin over time is suppressed, and the decrease in the ratio of the area of the fluororesin in the surface layer is also suppressed. The form in which the heating means is provided in the transport member is not particularly limited, but it is preferable that the heating means is provided integrally with other members constituting the transport member, such as the surface layer and the base material.
[0027] Specific examples of the heating means are not particularly limited, and various known means can be used, such as a heater and a means for generating hot air.
[0028] <<Drying equipment, printing equipment>> The drying device of the present embodiment is a device that dries a contacted member to which a liquid composition has been applied by heating it, and includes the above-mentioned conveying member and the like. The printing apparatus of the present embodiment also includes a liquid composition applying means for applying the liquid composition to a contacted member, the transport member, and the like. The drying device and the printing device will be described with reference to Fig. 2. Fig. 2 is a schematic diagram showing an example of a printing device using continuous paper. The printing device 100 shown in Fig. 2 has a contacted member supplying means 1, a liquid composition applying means 2, a heating member 3, a transporting member 4, and a contacted member collecting means 6. The printing device 100 also has a drying device 50, but the drying device 50 may be an integrated device with the printing device 100 or a separate independent device.
[0029] <Contacted member supply means> The contacted member supplying means 1 is driven to rotate, thereby supplying the contacted member 7, which is stored in a roll shape, to a transport path 8 in the printing apparatus 100. The transport direction of the contacted member 7 on the transport path 8 is indicated by an arrow D. The contacted member supplying means 1 adjusts the rotational drive to transport the contacted member 7 at a high speed of, for example, 50 m / min or more.
[0030] The contacted member 7 is a sheet-like transported object that is continuous in the transport direction D of the printing device 100, and is specifically a recording medium such as continuous paper. Examples of continuous paper include rolled paper rolled into a roll and continuous paper folded at predetermined intervals. The contacted member 7 is transported along a transport path 8 between the contacted member supplying means 1 and the contacted member collecting means 6. The length of the contacted member 7 in the transport direction D is at least longer than the length of the transport path 8 for the contacted member 7 provided between the contacted member supplying means 1 and the contacted member collecting means 6. The printing device 100 of this embodiment uses the contacted member 7 that is continuous in the transport direction D of the printing device 100 and transports the contacted member 7 at high speed, so that a large tension is applied to the contacted member 7 between the contacted member supplying means 1 and the contacted member collecting means 6.
[0031] <Liquid composition application means> The liquid composition applying means 2 is an inkjet ejection head having a plurality of nozzle rows in which a plurality of nozzles are arranged, and is provided so that the direction of ejection of ink from the nozzles faces the transport path 8 of the contacted member 7. In this way, the liquid composition applying means 2 sequentially ejects ink of each color, magenta (M), cyan (C), yellow (Y), and black (K), as liquid compositions onto the contacted member 7. Note that the colors of the ejected ink are not limited to these, and may be white, gray, silver, gold, green, blue, orange, violet, or other colors. In the present embodiment, the liquid composition is described as an example in which the liquid composition is ink, but other liquid compositions may be used. For example, the liquid composition may be ink, a pre-treatment liquid applied to aggregate coloring materials contained in the ink, a post-treatment liquid applied to protect the surface of the applied ink, and a liquid for forming an electric circuit in which inorganic particles such as metal are dispersed, and the like, or a liquid in which these are appropriately mixed or layered. In the present embodiment, the liquid composition is applied to the contacted member 7 by an inkjet discharge head, but the liquid composition may be applied by other means. For example, various known means such as spin coating, spray coating, gravure roll coating, reverse roll coating, and bar coating can be used.
[0032] <Heating material> The heating member 3 heats and dries the liquid composition applied to the contacted member 7 from the back side of the surface of the contacted member 7 having the area where the liquid composition is applied. The means for heating the liquid composition is not particularly limited, and various known means can be used, such as a means for blowing hot air or a means for drying the back side of the contacted member 7 by contacting it with a flat heater or the like.
[0033] Furthermore, the heating member 3 is provided near the transport member 4 described below, and as a result, the surface temperature of the transport member may become high (e.g., 100° C. or higher) during use. In this manner, when the transport member is used in an environment where the surface temperature of the transport member becomes high, detachment of the fluororesin from the transport member is likely to become evident, and therefore it is preferable to use the transport member of the present disclosure.
[0034] In this application, the heating means and the heating member are clearly distinguished terms. As described above, the heating means is a means for applying heat to the contacted member through the surface layer, and is provided as one of the means constituting the transport member. On the other hand, the heating member is a member that is not a member that applies heat to the contacted member through the surface layer, and is a member that is incorporated into the drying device or the printing device as a member separate from the transport member.
[0035] <Transportation parts> The transport member 4 is a columnar or cylindrical roller, and while transporting the contacted member 7, changes the transport direction D of the contacted member 7. The transport member 4 transports the contacted member 7 while coming into contact with the surface of the contacted member 7 having an area to which the liquid composition is applied.
[0036] As described above, in the printing device 100 of this embodiment, the contacted member supplying means 1 transports the contacted member 7 at 50 m / min or more. When transporting at such a high speed, as shown in Fig. 2, when the transport direction of the contacted member 7 is changed by the transport member 4, a large pressure is applied between the transport member 4 and the contacted member 7. This makes it easier for the fluororesin of the transport member to come off, so it is preferable to use the transport member of the present disclosure, which suppresses the detachment of the fluororesin.
[0037] As described above, the printing device 100 of this embodiment transports the contacted member 7 that continues in the transport direction D of the printing device 100, so a large tension is applied to the contacted member 7 between the contacted member supply means 1 and the contacted member recovery means 6. In such a case, as shown in Fig. 2, when the transport direction of the contacted member 7 to which a large tension is applied is changed by the transport member 4, a large pressure is applied between the transport member 4 and the contacted member 7. This makes it easier for the fluororesin of the transport member to be detached, so it is preferable to use the transport member of the present disclosure, which suppresses the detachment of the fluororesin.
[0038] Furthermore, when the conveying member 4 is a roller-shaped conveying roller, as shown in FIG. 2, the contacted member 7 is wound around the conveying roller, thereby changing the conveying direction of the contacted member 7. In this case, the winding ratio of the contacted member 7 to the conveying roller is preferably 10% or more, more preferably 15% or more, and even more preferably 20% or more. By being 10% or more, the pressure per unit area generated between the conveying roller and the contacted member 7 decreases, and the detachment of the fluororesin from the conveying member is suppressed. Furthermore, the winding ratio of the contacted member 7 to the conveying roller is preferably 90% or less, more preferably 70% or less, and even more preferably 50% or less. By being 50% or less, the contacted member 7 can be conveyed appropriately.
[0039] The "winding ratio" in this embodiment will be described with reference to Fig. 3. Fig. 3 is a schematic diagram showing that the contacted member is in contact with the conveying member. As shown in Fig. 3, in the case where the contacted member 7 is in contact with the roller-shaped conveying member 4 by being wound around it, the "winding ratio" indicates the ratio of the circumferential length X of the conveying member 4 between 9a and 9b on the side where the contacted member 7 and the conveying member 4 are in contact to the total circumferential length of the conveying member 4, when one end of the contacted member separated from the conveying member is 9a and the other end is 9b.
[0040] 2 does not have a heating means for applying heat to the contacted member 7 through the surface layer, but may have one. When the conveying member 4 has a heating means, the surface temperature of the conveying member may be high (e.g., 100° C. or higher) during use. In this way, when the conveying member is used in an environment where the surface temperature of the conveying member is high, detachment of the fluororesin from the conveying member is likely to become apparent, so it is preferable to use the conveying member of the present disclosure.
[0041] <Contacted member recovery means> The contacted member recovery means 6 is rotationally driven to wind up the contacted member 7 on which an image has been formed by applying the liquid composition, and store it in a roll shape.
[0042] <<Print method>> The printing method of the present embodiment includes a liquid composition applying step of applying the liquid composition to a contacted member, and a transport step of transporting the contacted member by bringing a transport member into contact with the contacted member.
[0043] <Liquid composition application step> The liquid composition applying step is a step of applying a liquid composition such as ink to the contacted member 7 supplied from the contacted member supplying means 1. As a result, a region where the liquid composition is applied is formed on the contacted member 7.
[0044] <Drying process> The drying step is a step of drying the applied liquid composition by heating it using the heating member 3 after the liquid composition application step. Drying is preferably performed to the extent that the contacted member 7 does not feel sticky. When a heating means is incorporated in the transport member, drying may be performed by the transport member.
[0045] <Transportation process> The transporting step is a step of transporting the contacted member 7 by contacting the contacted member 7 with the transporting member 4 after the drying step. The transporting step may be performed either before or after the liquid composition applying step. The transporting step may be performed either before or after the drying step.
[0046] <<Liquid composition>> The liquid composition in the present embodiment is not particularly limited, but examples thereof include ink, a pre-treatment liquid applied to aggregate coloring materials contained in the ink, a post-treatment liquid applied to protect the surface of the applied ink, and a liquid for forming an electric circuit or the like in which inorganic particles such as metal are dispersed. These can be used in any known composition as appropriate. Hereinafter, as an example, a case where ink is used as the liquid composition will be described.
[0047] <Ink> The organic solvent, water, coloring material, resin, wax, additives, and the like used in the ink will be described below.
[0048] -Organic solvents- The organic solvent is not particularly limited, and any water-soluble organic solvent can be used. Examples of the organic solvent include polyhydric alcohols, ethers such as polyhydric alcohol alkyl ethers and polyhydric alcohol aryl ethers, nitrogen-containing heterocyclic compounds, amides, amines, and sulfur-containing compounds. Specific examples of polyhydric alcohols include ethylene glycol, diethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 3-methyl-1,3-butanediol, triethylene glycol, polyethylene glycol, polypropylene glycol, 1,2-pentanediol, 1,3-pentanediol, and 1,4-pentanediol. Examples of such hexanediol include 2,4-pentanediol, 1,5-pentanediol, 1,2-hexanediol, 1,6-hexanediol, 1,3-hexanediol, 2,5-hexanediol, 1,5-hexanediol, glycerin, 1,2,6-hexanetriol, 2-ethyl-1,3-hexanediol, ethyl-1,2,4-butanetriol, 1,2,3-butanetriol, 2,2,4-trimethyl-1,3-pentanediol, and petriol. Examples of polyhydric alcohol alkyl ethers include ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, tetraethylene glycol monomethyl ether, and propylene glycol monoethyl ether. Examples of polyhydric alcohol aryl ethers include ethylene glycol monophenyl ether and ethylene glycol monobenzyl ether. Examples of the nitrogen-containing heterocyclic compounds include 2-pyrrolidone, N-methyl-2-pyrrolidone, N-hydroxyethyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, ε-caprolactam, and γ-butyrolactone. Examples of the amides include formamide, N-methylformamide, N,N-dimethylformamide, 3-methoxy-N,N-dimethylpropionamide, and 3-butoxy-N,N-dimethylpropionamide. Examples of the amines include monoethanolamine, diethanolamine, and triethylamine. Examples of sulfur-containing compounds include dimethyl sulfoxide, sulfolane, and thiodiethanol. Other organic solvents include propylene carbonate, ethylene carbonate, and the like. It is preferable to use an organic solvent having a boiling point of 250° C. or less, since this not only functions as a wetting agent but also provides good drying properties.
[0049] As the organic solvent, polyol compounds having 8 or more carbon atoms and glycol ether compounds are also suitably used. Specific examples of polyol compounds having 8 or more carbon atoms include 2-ethyl-1,3-hexanediol and 2,2,4-trimethyl-1,3-pentanediol. Specific examples of the glycol ether compound include polyhydric alcohol alkyl ethers such as ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, tetraethylene glycol monomethyl ether, and propylene glycol monoethyl ether; and polyhydric alcohol aryl ethers such as ethylene glycol monophenyl ether and ethylene glycol monobenzyl ether.
[0050] In particular, when a resin is used as the ink composition, N,N-dimethyl-β-butoxypropionamide, N,N-dimethyl-β-ethoxypropionamide, 3-ethyl-3-hydroxymethyloxetane, and propylene glycol monomethyl ether are preferred. These may be used alone or in combination of two or more. Among these, amide solvents such as 3-butoxy-N,N-dimethylpropionamide and 3-methoxy-N,N-dimethylpropionamide are particularly preferred, as they promote the film-forming properties of the resin and can exhibit high abrasion resistance.
[0051] The boiling point of the organic solvent is preferably 180°C or higher and 250°C or lower. If the boiling point is 180°C or higher, the evaporation rate during drying can be appropriately adjusted, leveling can be sufficiently performed, surface irregularities can be reduced, and gloss can be improved. Conversely, if the boiling point is higher than 250°C, the drying property is low and long drying times may be required. With the recent increase in printing speed, the time it takes for the ink to dry has become the rate limiting factor, and it is necessary to shorten the drying time, so long drying times are not preferred.
[0052] The content of the organic solvent in the ink is not particularly limited and can be appropriately selected depending on the purpose. From the viewpoints of the drying property and ejection reliability of the ink, however, the content is preferably from 10% by mass to 60% by mass, and more preferably from 20% by mass to 60% by mass.
[0053] The content of the amide solvent in the ink is preferably from 0.05% to 10% by mass, and more preferably from 0.1% to 5% by mass.
[0054] -water- The water content in the ink is not particularly limited and can be appropriately selected depending on the purpose. From the viewpoints of the drying property and ejection reliability of the ink, however, it is preferably from 10% by mass to 90% by mass, and more preferably from 20% by mass to 60% by mass.
[0055] -Coloring materials- The coloring material is not particularly limited, and pigments and dyes can be used. As the pigment, an inorganic pigment or an organic pigment can be used. These pigments can be used alone or in combination of two or more. Also, mixed crystals can be used as the pigment. Examples of pigments that can be used include black pigments, yellow pigments, magenta pigments, cyan pigments, white pigments, green pigments, orange pigments, glossy pigments such as gold and silver pigments, and metallic pigments. As inorganic pigments, titanium oxide, iron oxide, calcium carbonate, barium sulfate, aluminum hydroxide, barium yellow, cadmium red, chrome yellow, as well as carbon black produced by known methods such as the contact method, furnace method, and thermal method can be used. As organic pigments, azo pigments, polycyclic pigments (e.g., phthalocyanine pigments, perylene pigments, perinone pigments, anthraquinone pigments, quinacridone pigments, dioxazine pigments, indigo pigments, thioindigo pigments, isoindolinone pigments, quinophthalone pigments, etc.), dye chelates (e.g., basic dye chelates, acid dye chelates, etc.), nitro pigments, nitroso pigments, aniline black, etc. can be used. Among these pigments, those having good affinity with the solvent are preferably used. In addition, resin hollow particles and inorganic hollow particles can also be used. Specific examples of pigments for black colors include carbon blacks (CI Pigment Black 7) such as furnace black, lamp black, acetylene black, and channel black; metals such as copper, iron (CI Pigment Black 11), and titanium oxide; and organic pigments such as aniline black (CI Pigment Black 1). In addition, for color, CI Pigment Yellow 1, 3, 12, 13, 14, 17, 24, 34, 35, 37, 42 (yellow iron oxide), 53, 55, 74, 81, 83, 95, 97, 98, 100, 101, 104, 108, 109, 110, 117, 120, 138, 150, 153, 155, 180, 185, 213, CI Pigment Yellow Range 5, 13, 16, 17, 36, 43, 51, CI Pigment Red 1, 2, 3, 5, 17, 22, 23, 31, 38, 48:2, 48:2 (Permanent Red 2B (Ca)), 48:3, 48:4, 49:1, 52:2, 53:1, 57:1 (Brilliant Carmine 6B), 60:1, 63:1, 63:2, 64:1, 81, 83, 88 , 101 (red oxide), 104, 105, 106, 108 (cadmium red), 112, 114, 122 (quinacridone magenta), 123, 146, 149, 166, 168, 170, 172, 177, 178, 179, 184, 185, 190, 193, 202, 207, 208, 209, 213, 219, 224, 254, 264, CI Pigment Violet 1 (Rhodamine Lake), 3, 5:1, 16, 19, 23, 38; CI Pigment Blue 1, 2, 15 (Phthalocyanine Blue), 15:1, 15:2, 15:3, 15:4 (Phthalocyanine Blue), 16, 17:1, 56, 60, 63; CI Pigment Green 1, 4, 7, 8, 10, 17, 18, 36, etc. The dye is not particularly limited, and acid dyes, direct dyes, reactive dyes, and basic dyes can be used. One type of dye may be used alone, or two or more types may be used in combination. Dyes include, for example, CI Acid Yellow 17, 23, 42, 44, 79, 142, CI Acid Red 52, 80, 82, 249, 254, 289, CI Acid Blue 9, 45, 249, CI Acid Black 1, 2, 24, 94, CI Food Black 1, 2, CI Direct Yellow 1, 12, 24, 33, 50, 55, 58, 86, 132, 142, 144, 173, CI Direct Red 1, 4, 9, 80, 81, 225, 227, CI Direct Blue 1, 2, 15, 71, 86, 87, 98, 165, 199, 202, CI Directed Black 19, 38, 51, 71, 154, 168, 171, 195, CI Reactive Red 14, 32, 55, 79, 249, CI Reactive Black 3, 4, 35.
[0056] The content of the coloring material in the ink is preferably from 0.1% to 15% by mass, and more preferably from 1% to 10% by mass, from the viewpoints of improving image density, good fixing property and ejection stability.
[0057] Methods for dispersing a pigment to obtain an ink include a method in which a hydrophilic functional group is introduced into the pigment to make it a self-dispersing pigment, a method in which the surface of the pigment is coated with a resin and then dispersed, and a method in which a dispersant is used to disperse the pigment. As a method for introducing a hydrophilic functional group into a pigment to make it a self-dispersing pigment, for example, a method in which a functional group such as a sulfone group or a carboxyl group is added to a pigment (e.g., carbon) to make it dispersible in water can be mentioned. As a method for dispersing a pigment by coating its surface with a resin, there is a method in which the pigment is encapsulated in a microcapsule to make it dispersible in water. This can be called a resin-coated pigment. In this case, it is not necessary for all of the pigments blended in the ink to be coated with resin, and uncoated or partially coated pigments may be dispersed in the ink. Examples of the method for dispersing using a dispersant include a method for dispersing using a known low molecular weight dispersant or a polymeric dispersant, typified by a surfactant. As the dispersant, for example, anionic surfactants, cationic surfactants, amphoteric surfactants, nonionic surfactants, etc. can be used depending on the pigment. As the dispersant, RT-100 (nonionic surfactant) manufactured by Takemoto Oil Co., Ltd. and sodium naphthalenesulfonate formalin condensate can also be suitably used. The dispersants may be used alone or in combination of two or more.
[0058] -Pigment dispersion- It is possible to obtain ink by mixing a pigment with materials such as water or an organic solvent, or it is also possible to manufacture ink by mixing a pigment with other materials such as water and a dispersant to prepare a pigment dispersion, and then mixing the resulting mixture with materials such as water or an organic solvent. The pigment dispersion is obtained by mixing and dispersing water, a pigment, a pigment dispersant, and other components as necessary, and adjusting the particle size. Dispersion is preferably performed using a dispersing machine. The particle size of the pigment in the pigment dispersion is not particularly limited, but the maximum frequency in terms of the maximum number is preferably 20 nm or more and 500 nm or less, more preferably 20 nm or more and 150 nm or less, in order to improve the dispersion stability of the pigment and the image quality such as ejection stability and image density. The particle size of the pigment can be measured using a particle size analyzer (Nanotrac Wave-UT151, manufactured by Microtrac Bell Co., Ltd.). The pigment content in the pigment dispersion is not particularly limited and can be appropriately selected depending on the purpose. From the viewpoints of obtaining good ejection stability and increasing image density, the pigment content is preferably from 0.1% by mass to 50% by mass, and more preferably from 0.1% by mass to 30% by mass. It is preferable to filter out coarse particles from the pigment dispersion using a filter or a centrifugal separator, and degas the pigment dispersion, if necessary.
[0059] -resin- The type of resin contained in the ink is not particularly limited and can be appropriately selected depending on the purpose. Examples of the resin include urethane resin, polyester resin, acrylic resin, vinyl acetate resin, styrene resin, butadiene resin, styrene-butadiene resin, vinyl chloride resin, acrylic styrene resin, and acrylic silicone resin. Resin particles made of these resins may be used. The resin particles may be dispersed in water as a dispersion medium to form a resin emulsion, and the resin particles may be mixed with materials such as coloring materials and organic solvents to obtain an ink. The resin particles may be appropriately synthesized or may be commercially available. These may be used alone or in combination of two or more types of resin particles.
[0060] Among these, urethane resin particles have a large tackiness of an image formed by applying an ink using the urethane resin particles, which deteriorates blocking resistance, so it is preferable to use them in combination with other resin particles, but the strength of the tackiness of the urethane resin particles allows the image to be formed firmly and improves fixability. In addition, urethane resin particles with a glass transition temperature (Tg) of -20°C or more and 70°C or less can have a larger tackiness of an image formed by applying an ink using the urethane resin particles, and can further improve fixability. Among the above resins, acrylic resin particles using acrylic resin are widely used because they have excellent discharge stability and are inexpensive. However, since they have poor abrasion resistance, it is preferable to use them in combination with elastic urethane resin particles.
[0061] The volume average particle size of the resin particles is not particularly limited and can be appropriately selected depending on the purpose. From the viewpoint of obtaining good fixing property and high image hardness, however, it is preferably from 10 nm to 1,000 nm, more preferably from 10 nm to 200 nm, and particularly preferably from 10 nm to 100 nm. The volume average particle size can be measured, for example, using a particle size analyzer (Nanotrac Wave-UT151, manufactured by Microtrac-Bell Co., Ltd.).
[0062] The resin content is not particularly limited and can be appropriately selected depending on the purpose. From the viewpoints of fixation property and storage stability of the ink, however, the resin content is preferably from 1% by mass to 30% by mass, and more preferably from 5% by mass to 20% by mass, of the total amount of the ink.
[0063] The particle size of the solid content in the ink is not particularly limited and can be appropriately selected according to the purpose. In order to improve the image quality such as ejection stability and image density, the maximum frequency of the particle size of the solid content in the ink is preferably 20 nm or more and 1000 nm or less, more preferably 20 nm or more and 150 nm or less, in terms of the maximum number. The solid content includes resin particles, pigment particles, etc. The particle size can be measured using a particle size analyzer (Nanotrac Wave-UT151, manufactured by Microtrac Bell Co., Ltd.).
[0064] -wax- By including wax in the ink, it is possible to improve the abrasion resistance, and by using it in combination with a resin, it is possible to improve the glossiness. As the wax, polyethylene wax is preferable. As the polyethylene wax, a commercially available product can be used, and examples of the commercially available product include AQUACER531 (manufactured by BYK Japan), Polylon P502 (manufactured by Chukyo Yushi), Aquapetro DP2502C (manufactured by Toyo Adle Co., Ltd.), and Aquapetro DP2401 (manufactured by Toyo Adle Co., Ltd.). These may be used alone or in combination of two or more types. The content of the polyethylene wax is preferably 0.05% by mass or more and 2% by mass or less, more preferably 0.05% by mass or more and 0.5% by mass or less, based on the total amount of the ink. If the content is 0.05% by mass or more and 2% by mass or less, it is effective enough to improve the abrasion resistance and gloss. If the content is 0.45% by mass or less, the storage stability and ejection stability of the ink are particularly good, making it more suitable for use in the inkjet method.
[0065] -Additives- If necessary, surfactants, antifoaming agents, antiseptics, antifungals, rust inhibitors, pH adjusters, etc. may be added to the ink.
[0066] <<Contacted member>> The contact member can be any recording medium without particular limitations, such as ordinary paper, glossy paper, special paper, cloth, etc., but is particularly suitable for use with low-permeability recording media (also called low-absorbency recording media). The term "low-permeability recording medium" refers to a recording medium having a surface with low water permeability, absorbency, or adsorption, and includes materials that have many cavities inside but are not open to the outside. Examples of low-permeability recording media include coated paper used in commercial printing and recording media such as paperboard coated with recycled paper pulp in the middle and back layers.
[0067] <Low permeability recording media> Examples of low-permeability recording media include recording media such as coated paper having a support and a surface layer provided on at least one side of the support, and further having other layers as necessary.
[0068] In a recording medium having a support and a surface layer, the amount of pure water transferred to the recording medium in a contact time of 100 ms measured with a dynamic scanning absorptiometer was 2 mL / m 2 More than 35mL / m 2 Less than 2mL / m is preferable. 2 More than 10mL / m 2 The following is more preferred:
[0069] If the amount of ink and pure water transferred during a contact time of 100 ms is too small, beading may occur easily, whereas if the amount is too large, the ink dot diameter after image formation may become smaller than the desired diameter.
[0070] The amount of pure water transferred to the recording medium in a contact time of 400 ms measured using a dynamic scanning absorptiometer was 3 mL / m 2 More than 40mL / m 2 Less than 3 mL / m is preferable. 2 More than 10mL / m2 The following is more preferred:
[0071] If the amount of transfer at a contact time of 400 ms is small, the drying property will be insufficient, and if it is too much, the gloss of the image area after drying may be easily reduced. The amount of pure water transferred to the recording medium at contact times of 100 ms and 400 ms can both be measured on the side of the recording medium having the surface layer.
[0072] Here, the dynamic scanning absorptometer (DSA, Journal of the Japan Paper and Pulp Technology Association, Vol. 48, May 1994, pp. 88-92, Shigenori Kuga) is an instrument that can accurately measure the amount of absorbed liquid in an extremely short time. The dynamic scanning absorptometer automates the measurement by directly reading the absorption speed from the movement of the meniscus in the capillary, scanning the sample in a disk shape with the absorption head in a spiral shape, automatically changing the scanning speed according to a preset pattern, and measuring the required number of points on one sample.
[0073] The liquid supply head for the paper sample is connected to the capillary via a Teflon tube, and the position of the meniscus in the capillary is automatically read by an optical sensor. Specifically, the transferred amount of pure water or ink can be measured using a dynamic scanning absorptiometer (K350 series D type, manufactured by Kyowa Seiko Co., Ltd.).
[0074] The transfer amounts at a contact time of 100 ms and a contact time of 400 ms can be calculated by interpolation from the measured values of the transfer amounts at contact times adjacent to each contact time.
[0075] -Support- The support is not particularly limited and can be appropriately selected depending on the purpose. Examples of the support include paper mainly made of wood fibers, and sheet-like materials such as nonwoven fabric mainly made of wood fibers and synthetic fibers. The thickness of the support is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 50 μm to 300 μm.2 ~290g / m 2 is preferred.
[0076] -Surface layer- The surface layer contains a pigment and a binder, and may further contain a surfactant and other components as required. As the pigment, an inorganic pigment or a combination of an inorganic pigment and an organic pigment can be used. Examples of inorganic pigments include kaolin, talc, heavy calcium carbonate, light calcium carbonate, calcium sulfite, amorphous silica, titanium white, magnesium carbonate, titanium dioxide, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, zinc hydroxide, and chlorite. The amount of inorganic pigment added is preferably 50 parts by mass or more per 100 parts by mass of the binder. Examples of organic pigments include water-soluble dispersions of styrene-acrylic copolymer particles, styrene-butadiene copolymer particles, polystyrene particles, polyethylene particles, etc. The amount of organic pigment added is preferably 2 to 20 parts by mass with respect to 100 parts by mass of the total pigments in the surface layer. As the binder, it is preferable to use an aqueous resin. As the aqueous resin, at least one of a water-soluble resin and a water-dispersible resin can be suitably used. The water-soluble resin is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include polyvinyl alcohol, cation-modified polyvinyl alcohol, acetal-modified polyvinyl alcohol, polyester, polyurethane, and polyester and polyurethane. The surfactant contained in the surface layer as necessary is not particularly limited and can be appropriately selected depending on the purpose, but any of anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants can be used. The method for forming the surface layer is not particularly limited and can be appropriately selected depending on the purpose. The method can be performed by impregnating or coating the support with the liquid that constitutes the surface layer. The amount of the liquid that constitutes the surface layer is not particularly limited and can be appropriately selected depending on the purpose. The amount of the liquid that constitutes the surface layer that is applied ... 2 ~20g / m 2is preferred, and 1 g / m 2 ~15g / m 2 is more preferred. EXAMPLES
[0077] Examples of the present invention will be described below, but the present invention is not limited to these examples.
[0078] <Preparation example of black pigment dispersion> Carbon black (NIPEX160, manufactured by Degussa, BET specific surface area 150m 2 20 g of 20 mM 2H 2 O (average primary particle size 20 nm, pH 4.0, DBP oil absorption 620 g / 100 g), 20 mmol of a compound represented by the following structural formula (1), and 200 mL of ion-exchanged highly pure water were mixed in a Silverson mixer (6,000 rpm) at room temperature. When the pH of the resulting slurry was higher than 4, 20 mmol of nitric acid was added. After 30 minutes, sodium nitrite (20 mmol) dissolved in a small amount of highly pure ion-exchanged water was slowly added to the mixture. The mixture was then heated to 60°C with stirring and reacted for 1 hour. A modified pigment was produced in which a compound represented by the following structural formula (1) was added to carbon black. Next, the pH was adjusted to 10 with an aqueous NaOH solution, and after 30 minutes, a modified pigment dispersion was obtained. The dispersion containing the pigment bonded to at least one geminal bisphosphonic acid group or geminal bisphosphonic acid sodium salt and ion-exchanged highly pure water were subjected to ultrafiltration using a dialysis membrane, and further subjected to ultrasonic dispersion to obtain a self-dispersed black pigment dispersion having a bisphosphonic acid group as a hydrophilic functional group with a pigment solids concentration of 16 mass%.
[0079] [ka]
[0080] <Preparation Example of Liquid Composition (Ink)> A liquid composition (ink) was obtained by mixing 50.00 mass% black pigment dispersion (pigment solids concentration 16%), 2.22 mass% polyethylene wax AQUACER 531 (non-volatile content 45 mass%, manufactured by BYK Japan), 30.00 mass% 3-ethyl-3-hydroxymethyloxetane, 10.0 mass% propylene glycol monopropyl ether, 2.00 mass% silicone surfactant (TEGO Wet 270, manufactured by Tomoe Engineering Co., Ltd.), and ion-exchanged water (remaining amount). The mixture was stirred for 1 hour and then filtered through a membrane filter having an average pore size of 1.2 μm.
[0081] <Manufacturing example of conveying member> Example 1 The surface of an aluminum hollow roller substrate (material: JIS A6061) with a diameter of 80 mm was treated by anodizing the aluminum in an aqueous sulfuric acid solution (sulfuric acid anodizing treatment). More specifically, electrodes were attached to the ends of the hollow roller substrate, and it was submerged in a 15 wt% aqueous sulfuric acid solution adjusted to 0°C, and a current of 1.0 A / dm was applied to the metal rod as the anode. 2 Electrolysis was performed for 0.5 hours at a current density of 1000 rpm, and a sulfate alumite coating (a layer containing aluminum oxide and in which sulfur components are detected) was deposited to form a support layer with a thickness of 29 μm. The surface was thoroughly washed with pure water, and the roller was immersed in a dispersion liquid in which a PTFE dispersion (Fluon manufactured by AGC) was diluted to a solid content concentration of 10% or less, and then air-dried once. The hollow roller after air-drying was rotated at a speed of 10 rpm, and a polishing process was performed once by pressing and wiping with a polyester-nylon mixed fiber (product name: Toray, manufactured by Toray Industries, Inc.). The hollow roller thus obtained was integrated with a halogen lamp as a heating means to obtain a conveying member of Example 1. The Vickers hardness of the conveying member of Example 1 was measured according to the test method of JIS Z2244 and was 350 Hv or more and 450 Hv or less.
[0082] (Examples 2 to 6) In Example 1, the type of substrate, the time of electrolytic treatment, the method of applying the resin, the number of times the resin was applied, and the number of times the hollow roller was polished were changed to those shown in Table 1 below, but the operations of Examples 2 to 6 were carried out in the same manner as in Example 1 to obtain a conveying member.
[0083] (Comparative Examples 1 to 3) In Example 1, the type of substrate, the time of electrolytic treatment, the method of applying the resin, the number of times the resin was applied, and the number of times the hollow roller was polished were changed to those shown in Table 2 below, but the operations in Comparative Examples 1 to 3 were carried out in the same manner as in Example 1 to obtain a conveying member.
[0084] Comparative Example 4 A PTFE dispersion (Fluon manufactured by AGC) diluted to a solid content concentration of 10% or less was sprayed onto the surface of an aluminum hollow roller substrate (material: JIS A6061) having a diameter of 80 mm using a two-fluid nozzle to form a coating film, which was then dried. This process was repeated three times. The hollow roller thus obtained was integrated with a halogen lamp as a heating means to obtain a conveying member of Comparative Example 1. In Comparative Example 4, no sulfuric acid anodizing treatment was performed.
[0085] Comparative Example 5 An aluminum hollow roller substrate (material: JIS A6061) having a diameter of 80 mm was not treated and was integrated with a halogen lamp as a heating means to obtain a conveying member of Comparative Example 5. Note that in Comparative Example 5, neither the sulfuric acid anodizing treatment nor the resin adhesion treatment was performed.
[0086] In addition, for the transport members produced in Examples 1 to 6 and Comparative Examples 1 to 5, the components detected in the support layer, the depth of the recesses in the support layer, and the thickness of the support layer are shown in the following Tables 1 and 2. The measurement methods for these are as follows.
[0087] [Components detected in the support layer] A cross section was formed at the center of the transport member in the longitudinal direction, and the cross section of the support layer was subjected to EDS elemental analysis to map the sulfur component, aluminum component, oxygen component, and silicon component. The following EDS detector and analysis software were used for the EDS elemental analysis. EDS detector: Thermo Fisher Scientific, thermoelectrically cooled SDD, detector UltraDry Analysis software: Thermo Fisher Scientific, Noran System 6 Ver.2.3.108
[0088] [Depth of recess in supporting layer] A test piece of 5 mm x 5 mm was cut out from the center of the longitudinal direction of the transport member, and a surface image (x100) of the test piece was obtained using an Olympus 3D measuring laser microscope LEXT. Next, image analysis was performed using the attached analysis software OLS4100 to calculate Ra (arithmetic mean height). Similarly, Ra was calculated at 10 arbitrary points, and the average of these was used as the depth of the recess.
[0089] [Support layer thickness] A test piece of 5 mm x 5 mm was cut out from the center of the longitudinal direction of the transport member, and a cross-sectional image (x100) of the test piece was obtained using an Olympus 3D measuring laser microscope LEXT. Next, the support layer portion was determined from the cross-sectional image, and the length of the perpendicular line drawn from the support layer surface toward the substrate in the support layer was measured using the attached analysis software. Similarly, the length was measured at 10 random locations, and the average of these was taken as the thickness of the support layer.
[0090] Next, the area ratio of the fluororesin before and after the contact friction test and the contact surface of the contacted member in contact with the conveying member after the contact load test were evaluated for the conveying members of Examples 1 to 6 and Comparative Examples 1 to 5. The evaluation results are shown in Tables 1 and 2 below. The evaluation methods are as follows.
[0091] [Evaluation of the proportion of fluororesin area] First, the center of the conveying member in the longitudinal direction was cut to prepare a cylindrical test piece with a width of 10 mm. Next, a contact friction test was performed by contacting an indenter with the surface of the test piece according to the following test conditions. Specifically, a Tribogear Type: 40 (manufactured by Shinto Scientific Co., Ltd.) was used as an abrasion tester, and the test piece was rotated on the stage of the abrasion tester. The top of the rotating test piece was brought into contact with the indenter to apply a contact friction load to the test piece. This contact friction test corresponds to the load of approximately 7 years of normal printing in an inkjet printing system (RICOH Pro VC60000, manufactured by Ricoh Co., Ltd.). (Test conditions) Indenter: φ10mm SUS ball indenter Load capacity: 10g Contact speed: 5000mm / min (80mm diameter test piece rotated at approximately 20rpm) Contact length: 150m (approximately 600 rotations of a test piece with a diameter of 80mm) ·Temperature: 25℃
[0092] Next, a 5 mm x 5 mm test piece including a portion that had been in contact with the indenter and a portion that had not been in contact with the indenter was cut out from the 10 mm wide cylindrical test piece.
[0093] EDS elemental analysis was performed on the surface of the cut-out test piece, and the ratio of the area where the fluororesin was present to the area of the surface layer was calculated. The result calculated from the part not in contact with the indenter was taken as the ratio of the area where the fluororesin was present before the contact friction test (the conveying member that was not actually used), and the result calculated from the part in contact with the indenter was taken as the ratio of the area where the fluororesin was present after the contact friction test. The ratio of the area where the fluororesin was present to the area of the surface layer was specifically calculated as follows. First, EDS elemental analysis was performed on the surface of the cut-out test piece, and the fluorine components were mapped. Next, the area where the fluororesin was present was calculated from the obtained data using analysis software. In the same manner, the area where the fluororesin was present was calculated at any five points, and the average value of these was adopted. Next, the average value was divided by the area of the surface layer used to calculate the area where the fluororesin was present to obtain the ratio of the area where the fluororesin was present. Here, the area of the surface layer used to calculate the area where the fluororesin was present refers to the non-contact area, which is the area of the surface layer where the indenter did not come into contact when calculating the ratio of the area where the fluororesin was present before the contact friction test. On the other hand, when calculating the ratio of the area where the fluororesin exists after the contact friction test, it represents the contact area, which is the area where the indenter of the surface layer comes into contact. The area where the fluorine component exists is defined as the area where the fluorine atom concentration is 1% or more. The measurement area in the EDS elemental analysis was 100 μm × 100 μm.
[0094] In addition, SEM observation and EDS elemental analysis were performed on the surface of the cut-out test piece, and the ratio of the area where the fluororesin attached to the non-recessed portion exists to the area of the surface layer was calculated. This calculation was performed on the portion where the indenter was not in contact (the conveying member that was not actually used). The ratio of the area where the fluororesin attached to the non-recessed portion exists to the area of the surface layer was specifically calculated as follows. First, an SEM image of the surface of the cut-out test piece was obtained, and the recessed portion and the non-recessed portion were identified. The SEM image was observed at 2000 times magnification. Next, EDS elemental analysis was performed on the surface of the cut-out test piece (within the range where the SEM image was obtained), and the fluorine component was mapped. Next, the area where the fluororesin attached to the non-recessed portion exists was calculated from the data obtained using analysis software and the SEM image. In the same manner, the area where the fluororesin attached to the non-recessed portion exists was calculated at any five points, and the average value of these was adopted. Next, the average value was divided by the area of the surface layer region used to calculate the area where the fluororesin attached to the non-recessed portion exists to obtain the ratio of the area where the fluororesin attached to the non-recessed portion exists. Here, the surface layer region used to calculate the area where the fluororesin exists refers to the non-contact region where the indenter of the surface layer does not come into contact. The region where the fluorine component exists is defined as the region where the fluorine atom concentration is 1% or more. The measurement area in the EDS elemental analysis was 100 μm × 100 μm.
[0095] The above SEM observation and EDS elemental analysis were carried out using the following scanning electron microscope, EDS detector, and analysis software. Scanning electron microscope: Carl Zeiss (SII), FIB / SEM cross beam device, NVision 40 EDS detector: Thermo Fisher Scientific, thermoelectrically cooled SDD, detector UltraDry Analysis software: Thermo Fisher Scientific, Noran System 6 Ver.2.3.108
[0096] Fig. 4 shows an SEM image (2000x) of the surface of the transport member of Example 1 before the contact friction test, and Fig. 5 shows an SEM image (2000x) of the surface of the transport member of Example 1 after the contact friction test. 6 shows the EDS elemental analysis results (fluorine component mapping results) of the surface of the transport member of Example 1 before the contact friction test, and FIG. 7 shows the EDS elemental analysis results (fluorine component mapping results) of the surface of the transport member of Example 1 after the contact friction test.
[0097] [Evaluation of the contact surface of the contacted member (evaluation of image defects)] First, a contact load test was conducted by contacting the surface of the transport member with a contacted member according to the following test conditions. Specifically, the transport member was rotated while contacting the transport member with the contacted member and applying surface pressure to apply a contact load. This contact load test corresponds to the load of approximately 7 years of normal printing in an inkjet printing system (RICOH Pro VC60000, manufactured by Ricoh Co., Ltd.). (Test conditions) Contact material: Lumi Art Gloss 130gsm (Stora Enso roll paper) Surface pressure: 50N / cm 2 Contact speed: 5000mm / min (80mm diameter test piece rotated at approximately 20rpm) Contact volume: 1500m (approximately 6000 rotations of a test piece with a diameter of 80 mm) ·Temperature: 25℃
[0098] Next, a printing device was prepared by incorporating one of the transport members after the contact load test into an inkjet printing system (RICOH Pro VC60000, manufactured by Ricoh Co., Ltd.), and a 50 m image was printed on a recording medium, which was a contacted member, using the adjusted liquid composition (ink). At this time, the transport speed of the contacted member was 50 m / min, and the winding ratio of the contacted member to the transport member was 20% or more and 50% or less. As the recording medium, a roll paper of Lumi Art Gloss 130 gsm (manufactured by Stora Enso, paper width 520.7 mm, low permeability recording medium) was used. The length of this roll paper in the transport direction was longer than the length of the transport path of the printing device. In addition, the incorporated transport member transported the recording medium while contacting the surface (printing surface) of the recording medium having an area where ink was applied, and the temperature of the surface of the transport member during transport was 140°C. After the printing of the image was completed, the image on the printed surface at about 50 m that had come into contact with the left, center, or right part of the conveying member was cut out to a size of 25 mm x 25 mm, and the state of the contact surface of the contacted member was visually observed from a position 30 cm away and evaluated according to the following evaluation criteria. The left part of the conveying member refers to a part that is 1 / 4 of the length of the conveying member from the left end in the longitudinal direction of the conveying member. The center part of the conveying member refers to a part that is 1 / 2 of the length of the conveying member from the left end in the longitudinal direction of the conveying member. The right part of the conveying member refers to a part that is 3 / 4 of the length of the conveying member from the left end in the longitudinal direction of the conveying member. (Evaluation Criteria) A + : There is no image defect of 30 μm or more that can be visually observed, and there is no image defect of 30 μm or less in all three places A: There is no image defect of 30 μm or more that can be visually observed, and an image defect of 30 μm or less has occurred in one out of three places. A - : There are no image defects of 30 μm or more that can be visually observed, and image defects of 30 μm or less have occurred in 2 to 3 places. B: Visually observed image defects of 30 μm or more occurred in one out of three locations. C: Visually observed image defects of 30 μm or more occurred in 2 to 3 of the 3 locations.
[0099] [Table 1]
[0100] [Table 2]
[0101] According to Table 1, in Examples 1 to 6, when the contact friction test was performed, the ratio of the area where the fluororesin was present to the area of the contact area, which is the area of the surface layer where the indenter contacts, was larger after the contact friction test than before the contact friction test. This is because the ratio of the area where the fluororesin was present was 23.0% or more of the area of the surface layer, and the fluororesin migrated to be embedded in the recesses after the contact friction test, and also spread and expanded in non-recesses. As a result, the occurrence of image defects was suppressed in Examples 1 to 6. Furthermore, in Examples 1, 4, and 5, the ratio of the area where the fluororesin was present after the contact friction test was large, so the occurrence of image defects was further suppressed.
[0102] On the other hand, according to Table 2, in Comparative Examples 1 to 3, when the contact friction test was performed, the ratio of the area where the fluororesin was present to the area of the contact area, which is the area of the surface layer that comes into contact with the indenter, was smaller after the contact friction test than before the contact friction test. This is because the ratio of the area where the fluororesin was present was less than 23.0% of the area of the surface layer, and even after the contact friction test, the fluororesin only migrated to be embedded in the recesses, and did not spread out and extend in non-recesses, but instead detached. As a result, image defects occurred in Comparative Examples 1 to 5.
[0103] Moreover, according to Comparative Example 4 in Table 2, when the transport member does not have a support layer containing anodized aluminum sulfate, most of the fluororesin is removed by the contact friction test, and image defects occur.
[0104] Moreover, according to Comparative Example 5 in Table 2, when the transport member did not have a fluororesin, image defects occurred. [Explanation of symbols]
[0105] 1 Contacted member supply means 2. Liquid composition application means 3 Heating element 4. Transporting parts 6 Contacted member recovery means 7 Contacted member 8. Transport Route 9a, 9b Ends where the contacted member separates from the conveying member 10. Transport member 11 Contacted member 50 Drying equipment 100 Printing equipment [Prior art documents] [Patent documents]
[0106] [Patent Document 1] JP 2018-66552 A [Patent Document 2] Japanese Patent Application Publication No. 1-15782
Claims
1. A conveying member that conveys a contacted member by contacting the contacted member, the transport member has a surface layer that comes into contact with the contacted member, the surface layer includes a support layer having a surface with a plurality of recesses and a fluororesin adhered to the support layer, the ratio of the area where the fluororesin is present to the area of the surface layer is 23.0% or more; The support layer contains alumite sulfate, A conveying member characterized in that, when a contact friction test is conducted in which an indenter is brought into contact with the surface layer in accordance with the following test conditions, in a contact region of the surface layer where the indenter comes into contact, a ratio of an area in which the fluororesin is present to an area of the contact region is larger after the contact friction test than before the contact friction test. [Test conditions] Indenter: φ10mm SUS ball indenter Load: 10g ・Contact speed: 5000mm / min ・Contact amount: 150m ・Temperature: 25℃
2. the support layer has a non-recessed portion on its surface, the non-recessed portion being an area other than the recessed portion; 2. The transport member according to claim 1, wherein a ratio of an area of the fluororesin adhering to the non-recessed portions to an area of the surface layer is 3.0% or more.
3. 3. The conveying member according to claim 1, wherein the depth of the recess is 0.4 μm or more and 1.0 μm or less.
4. 4. The conveying member according to claim 1, wherein the support layer has a thickness of 25.0 μm or more and 35.0 μm or less.
5. 5. The conveying member according to claim 1, which is in the form of a roller having a diameter of 50 mm or more and 600 mm or less.
6. A conveying member that conveys a contacted member by contacting the contacted member, the transport member has a surface layer that comes into contact with the contacted member, the surface layer includes a support layer having a surface with a plurality of recesses and a fluororesin adhered to the support layer, the ratio of the area where the fluororesin is present to the area of the surface layer is 23.0% or more; the support layer contains aluminum oxide and is a layer in which a sulfur component is detected; A conveying member characterized in that, when a contact friction test is conducted in which an indenter is brought into contact with the surface layer in accordance with the following test conditions, in a contact region of the surface layer where the indenter comes into contact, a ratio of an area in which the fluororesin is present to an area of the contact region is larger after the contact friction test than before the contact friction test. [Test conditions] Indenter: φ10mm SUS ball indenter Load: 10g ・Contact speed: 5000mm / min ・Contact amount: 150m ・Temperature: 25℃
7. 7. The transport member according to claim 1, further comprising a heating means for applying heat to the contacted member through the surface layer.
8. A drying device comprising a conveying member according to any one of claims 1 to 7.
9. A printing apparatus comprising: a liquid composition applying means for applying a liquid composition to the contacted member; and the transport member according to claim 1 .
10. a contact member supplying means for supplying the contact member; a contact member recovery means for recovering the contact member; a conveying path along which the contacted member supplied from the contacted member supplying means is conveyed until it is collected by the contacted member collecting means, The printing apparatus according to claim 9 , wherein the length of the contacted member in the transport direction is longer than the length of the transport path.
11. 11. The printing apparatus according to claim 9, wherein the transport speed of the contacted member is 50 m / min or more.
Citation Information
Patent Citations
Roller in fixing device
JP1979034839A
Heating and fixing roller
JP1982100459A
Heat fixing roller and its manufacture
JP1986072273A
Fixing device
JP1989015782A
Fixing roller
JP1997197872A